Journey to the forgotten river [videorecording] - Cobbler, Jonathan; Joubert, Beverly; Joubert, Dereck (The Society, 1990)
An overview of the rich and varied environment of the Linyanti River and Batswana including the warriors wild animals found in the Saudi bank.